EFEKTIVITAS PENGGUNAAN GOOGLE CLASSROOM PADA PEMBELAJARAN MATEMATIKA SELAMA PANDEMI COVID-19 MAN KOTABARU - Agus Syarifuddin (CENDEKIA: JURNAL ILMIAH PENDIDIKAN, 2022)
The aims of this research is to know the effective of the used the Google Classroom in mathematics learning of pandemic Covid-19 in students of class X IPA MAN Kotabaru with the indicator of effectiveness in learning, that is: the implementation of learning, effective of students, the result of learning students, and the respond of students. The method that used is the quantitative of the research that is a process finding knowledge which used the data questioner as instrument the analysis statement by what want to know. The result of the research showed that the application of Google Classroom in mathematics learning during of pandemic Covid-19 not effectively applied to class X IPA MAN Kotabaru with achievement of criteria: the average score of learning implementation that achieved was 3 and include the category of carried out with good. However, the use of Google Classroom media is enough to help carry out the mathematics learning of process, especially during of pandemic Covid-19, which requires schools to learn using an online system (on a network). Key words: the effectiveness of learning, Google Classsroom, Covid-19.